DESIGN OF BIOGAS COOLING PROCESSING FROM POME FOR (CSTR) CONTINUOUS STIRRED TANK REACTOR SYSTEM - endro wahju tjahjono; Arfiana Arfiana; Era Restu Finalis; Ali Nurdin (Majalah Ilmiah Pengkajian Industri, 2020)
POME (Palm Oil Mill Effluent) can be used as for biogas production, with the main content of (65%) methane gas (CH4) and 35% Carbon Dioxide (CO2), H2S, and H2O gases. Apart from being a gas fuel and a source of electricity generation, biogas from POME waste as well as a waste processor becomes more environmentally friendly (according to quality standards). In order to support the process production of biogas from POME by using Continuous Stirred Tank Reactors (CSTR), it is necessary to decrease POME’s temperature to meet the requirements of the reactor operating conditions. Cooling process by using a Cooling Tower through direct contact between fluids can be a good alternative to be used as a POME cooling method because of its effectiveness in heat exchange and smaller area needed than an open ponds. The type of cooling tower used is the Induced Draft Cooling Tower. In cooling tower design, the steps involved in determining the basic design, calculation of tower dimensions, basin, fan power, losses, and cooling air requirements. Based on the calculation, the tower dimensions determine a height of 5 m, length of 3.6 m, and width of 2.5 m, while the basin cooling tower dimensions determine a height of 2.7 m, length of 3.6 m, and width of 2.5 m, fan power of 5 hp. The cooling air requirement for the POME cooling process is 82,895.14 kg/hour. Keywords : POME; Cooling Tower; CSTR; Fuel; Biogas